(untitled) (Orchid Academia Siraha, 2024)
In this research, first principles calculations of NaVF3 perovskite are performed using the Quantum ESPRESSO software package. The structural, electronic, magnetic, and mechanical properties of NaVF3 are computed. The electronic structure reveals that it exhibits half-metallic ferromagnetism, with conducting nature in the spin-up channel and non-conducting in the spin-down channel. The half-metallicity and ferromagnetism in NaVF3 are further confirmed by the integral magnetic moment of 3 μB. The mechanical properties analysis reveals that NaVF3 is mechanically stable, ductile, and displays significant elastic anisotropy.